2019
DOI: 10.1177/0265407519883697
|View full text |Cite
|
Sign up to set email alerts
|

Affection Deprivation in Marital Relationships: An Actor-partner Interdependence Mediation Analysis

Abstract: The current study sought to assess the dyadic effects of affection deprivation in marital relationships. We used the tenets of affection exchange theory to examine the actor and partner effects between affectionate communication, affection deprivation, and mental and relational outcomes. Moreover, we tested whether affection deprivation mediated the association between affectionate communication and outcome variables. In terms of actor effects, affectionate communication was associated with husbands’ depressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
1
4
0
1
Order By: Relevance
“…Two clarifications should be noted. First, the means for affection deprivation in this study at all three time points were not particularly high, and certainly not significantly higher than what has been found in previous studies of deprivation (e.g., Floyd & Hesse, 2017;Hesse & Tian, 2020). Second, the means for our outcome variables were also not particularly problematic at first glance, meaning that individuals did not score as particularly lonely or depressed (for example) during the study.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…Two clarifications should be noted. First, the means for affection deprivation in this study at all three time points were not particularly high, and certainly not significantly higher than what has been found in previous studies of deprivation (e.g., Floyd & Hesse, 2017;Hesse & Tian, 2020). Second, the means for our outcome variables were also not particularly problematic at first glance, meaning that individuals did not score as particularly lonely or depressed (for example) during the study.…”
Section: Discussionsupporting
confidence: 40%
“…From an actor standpoint, deprivation was positively correlated with depression and loneliness for both husbands and wives, though it was negatively correlated with marital quality only for husbands. With respect to partner effects, the study found consistent negative effects from affectionate communication to deprivation for both husbands and wives, showing that the more an individual reported communicating affection to their spouse, the less likely their partner reported feeling deprived of affection (Hesse & Tian, 2020). Thus, AET's argument about the importance of a minimum amount of affection for relational and psychosocial health outcomes is supported by previous research.…”
Section: Affection Deprivationmentioning
confidence: 52%
See 1 more Smart Citation
“…Within the context of romantic relationships, affection deprivation was negatively correlated with relational satisfaction and closeness (Hesse & Mikkelson, 2017). A study of marital dyads found consistent negative partner effects from affectionate communication to deprivation for both husbands and wives, meaning that the more an individual reported communicating affection to a spouse, the less likely the spouse was to feel deprived of affection (Hesse & Tian, 2020). Finally, a recent panel study conducted during the initial months of the COVID‐19 pandemic found that, over the span of four weeks, affection deprivation at the beginning of the study predicted stress, loneliness, and depression at the end of the study (Hesse, Mikkelson, & Tian, 2021).…”
Section: Affection Deprivation and Excessive Affectionmentioning
confidence: 99%
“…La EIE presenta ventajas en comparación a otras escalas que miden el mismo constructo, principalmente debido a su brevedad, fácil administración y a su foco en la intimidad emocional percibida en una relación cercana. Esto ha implicado su amplia y creciente utilización en investigación en los últimos años, incluyendo personas en pareja, con buenos índices de confiabilidad, la mayoría de las veces incluso más altos que en el estudio original y manteniendo la estructura propuesta (Amichai-Hamburger, & Etgar, 2016;Carvalheira & Costa, 2015;Guschlbauer et al, 2019;Hesse & Tian, 2020;Lonza et al, 2020;Carvalheira et al, 2014;Šević et al, 2016;Štulhofer et al, 2020;Traeen et al, 2013;Veit et al, 2016). Pese a su amplio uso, se desconocen estudios que confirmen la estructura factorial de esta escala.…”
Section: Introductionunclassified